Unveiling Success: Exploring Strategies of Pre-service Teachers in Implementing Merdeka Curriculum in Indonesia - Mutmainah, Agnia; Widhiatama, Daniel Ari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The comprehensive understanding towards Merdeka Curriculum is crucial for pre-service teachers because they will be responsible for effectively implementing it with their pedagogical knowledge, but it was found that only two from nine pre-service teachers who have good understanding towards Merdeka curriculum. This study aims to explore the issue in-depth about the strategies used by pre-service teachers in understanding Merdeka curriculum through conducting a case study with a qualitative approach. The subjects of this research are the students of the English Education Department from two different private Universities in Yogyakarta who have joined PPL (Program Pengenalan Lapangan) and have comprehensive understanding towards the Merdeka curriculum. The study used interview, observation, and document analysis to collect the data. The findings of this study indicate that the strategies used by the pre-service teachers were looking for information from the internet, reading, having discussion, and practice. Besides, understanding the core principle of Merdeka Belajar Curriculum, they also put it into practice in class. The respondents also indicate that they are having applied the Merdeka curriculum into their teaching practice, but they faced difficulties in differentiated learning.